Near-infrared fluorescent probes for imaging of amyloid plaques in Alzheimer׳s disease - Hongjuan Tong; Kaiyan Lou; Wei Wang (Elsevier, 2015)
One of the early pathological hallmarks of Alzheimer׳s disease (AD) is the deposition of amyloid-β (Aβ) plaques in the brain. There has been a tremendous interest in the development of Aβ plaques imaging probes for early diagnosis of AD in the past decades. Optical imaging, particularly near-infrared fluorescence (NIRF) imaging, has emerged as a safe, low cost, real-time, and widely available technique, providing an attractive approach for in vivo detection of Aβ plaques among many different imaging techniques. In this review, we provide a brief overview of the state-of-the-art development of NIRF Aβ probes and their in vitro and in vivo applications with special focus on design strategies and optical, binding, and brain-kinetic properties.